Tubeless video-assisted thoracoscopic surgery (VATS) under non-intubated, intravenous anesthesia with spontaneous ventilation and no placement of chest tube postoperatively - Cui, Fei; Liu, Jun; Li, Shuben; Yin, Weiqiang; Xin, Xu; Shao, Wenlong; He, Jianxing (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Background: To assess the feasibility and safety of tubeless video-assisted thoracoscopic surgery (VATS) under non-intubated, intravenous anesthesia with spontaneous ventilation and no placement of a chest tube postoperatively compared with VATS under intubated anesthesia with single-lung mechanical ventilation. Methods: A total of 91 patients undergoing tubeless VATS (60 sympathectomies, 22 bullae resections, and 9 mediastinal tumor resections) between December 2012 and December 2015 were included. Additionally, 82 patients were treated by VATS by the same team while under intubated general anesthesia (52 sympathectomies, 19 bullae resections, and 11 mediastinal tumor resections). Comprehensive early outcome data, including intraoperative and postoperative variables, were compared between the subgroups. Results: In total, 89 patients in the tubeless group underwent an effective operation and exhibited good postoperative recovery, while 2 (one sympathectomy and one bullae resection) had their operation aborted for some reason. The tubeless group showed advantages in the postoperative fasting time, the mean duration of the postoperative hospital stay, and postoperative pain scores, while no significant difference was found in intraoperative blood loss, the operation time or postoperative complications between the tubeless group and the intubated group. Furthermore, 83% (49/59) of sympathectomies, 81% (17/21) of bullae resections, and 56% (5/9) of mediastinal tumor resections were achieved via day surgery. Conclusions: In this study, our experience has shown that tubeless VATS is a safe and feasible surgery with certain advantages in selected patients with thoracic disease and that we can achieve day surgery in these cases.